2021
DOI: 10.25082/amler.2022.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The mobile internet as a tool of education and as a means of intimidation and victimization in the field of Ecclesiastical Education

Abstract: The use of Information and Communication Technologies (ICT) has undoubtedly influenced children, adolescents, and young people's social interactions and behavior. The use of technology has not only positive but also negative consequences. In recent years, research has shifted from traditional bullying to new forms of bullying, such as cyberbullying. In Greece, there is a research gap in investigating this phenomenon among students of Ecclesiastical Schools. This paper investigates the frequency of bullying and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…As a key course for cultivating people by virtue, lessons are essential for talent cultivation [2]. e teaching effect courses in higher vocational colleges concern that it can provide high-quality talent support for the realization of the country's strategic goal of building a strong country [3]. Subsequently, the Ministry of Education clearly stated that "encouraging qualified colleges and universities to teach ideological and political courses based on an online and offline hybrid teaching model based on the application of high-quality online open courses.…”
Section: Introductionmentioning
confidence: 99%
“…As a key course for cultivating people by virtue, lessons are essential for talent cultivation [2]. e teaching effect courses in higher vocational colleges concern that it can provide high-quality talent support for the realization of the country's strategic goal of building a strong country [3]. Subsequently, the Ministry of Education clearly stated that "encouraging qualified colleges and universities to teach ideological and political courses based on an online and offline hybrid teaching model based on the application of high-quality online open courses.…”
Section: Introductionmentioning
confidence: 99%
“…With online education, as long as you have a mobile terminal with internet access, you can choose your favorite course of study online from anywhere. The Internet + education model refers to a new teaching concept that has emerged from the rapid development of the Internet [19][20][21]. It is not just a simple link between the Internet and education but respects education as the basis while injecting the Internet mindset into the whole education process, making full use of the convenience brought by the development of the Internet, and using Internet technology as much as possible in all aspects of education, to promote better and improve the efficiency and quality of education development.…”
Section: Internet + Educationmentioning
confidence: 99%
“…Nevertheless, the constant, unrestricted access to the Internet via mobile phone and the increase in mobile phone users has raised concerns around the world about mobile phone overuse and risk of addiction. According to the literature, mobile phone has become an integral part of everyday life and it is shown that some people become overly attached to their device that they experience separation anxiety when they do not have it with them (Cheever et al, 2014;King et al, 2013;Alpochoritis, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%